Analisis Kinerja Keuangan Terhadap Keputusan Pemberian Kredit Pada Bank Bri Kota Bengkulu - Nansi Rianindita; Yuli Yusnita (STIA Bengkulu, 2026)
This study aims to analyze the effect of financial performance on credit decision-making at Bank BRI Bengkulu City, focusing on credit risk and banking policies. The research method used is descriptive quantitative with a financial ratio analysis approach for the 2022–2024 period, including liquidity, solvency, profitability, and credit risk ratios. The results show that the financial performance of Bank BRI Bengkulu City positively and significantly affects credit decision-making. Improved liquidity and profitability increase management’s confidence in extending credit, while credit risk control through the 5C principle helps reduce potential non-performing loans. Therefore, good financial performance serves as a strategic foundation in strengthening sustainable credit decision-making.